2010
DOI: 10.1590/s0103-90162010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of ingredients with amino acid composition similar to the nutritional requirement of Nile tilapia

Abstract: The search for balanced diets, which may elicit improved growth of fish, requires appropriate selection of available protein sources. This study aims at clustering feedstuffs according to amino acid profile, determining which ones show essential amino acids (EAA) profiles closer to the ideal dietary amino acids requirements of Nile tilapia (Oreochromis niloticus), and studying the relationship among amino acids feedstuffs groups. Tabled data on EAA more cystine and tyrosine, in relation to lysine contents, of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Similar to the current study, a number of works have noted that intermediate ratios of 320 ingredient combinations perform better than combinations at either end of the ratio spectrum when replacing fish meal in the diet [e.g., Bicudo et al, 2010;El-Saidy and Gaber, 2003;Lim et al, 2007;Neto & Ostrensky, 2015]. In most cases, it has been postulated that imbalances in essential amino acids may be ameliorated, or minimally defective, at these intermediate ingredient ratios.…”
Section: Discussion 319supporting
confidence: 75%
See 1 more Smart Citation
“…Similar to the current study, a number of works have noted that intermediate ratios of 320 ingredient combinations perform better than combinations at either end of the ratio spectrum when replacing fish meal in the diet [e.g., Bicudo et al, 2010;El-Saidy and Gaber, 2003;Lim et al, 2007;Neto & Ostrensky, 2015]. In most cases, it has been postulated that imbalances in essential amino acids may be ameliorated, or minimally defective, at these intermediate ingredient ratios.…”
Section: Discussion 319supporting
confidence: 75%
“…irrespective of ingredient combinations, and diet intact protein level, as long as a reasonable 434 amino acid model is chosen and a fairly robust set of ingredient composition and digestibility of 39 data are available, as suggested by a recent principal component analyses of ingredient amino acid profiles with respect to tilapia ideal protein model (Bicudo et al,2010). The current study also suggests that using the EAA content of a fish meal control diet as targets for optimizing fish 438 meal replacement diets is inadequate; whereas the whole body or muscle amino acid pattern 439 are more useful as formulation targets, including the ratio of NEAA to EAA.…”
Section: Of 39mentioning
confidence: 99%
“…Deficiencies in EAAs reduce growth and feed efficiency, which increases the environmental impact of intensive aquaculture (Wilson ). Corn and co‐products fed to Nile tilapia are deficient in lysine and threonine (Bicudo et al ); we also observed low threonine availability.…”
Section: Discussionsupporting
confidence: 65%
“…), and histidine and valine in tilapia (Bicudo et al . ). While soybean has antinutritional factors that may reduce the digestibility of energy and nutrients (Francis et al .…”
Section: Introductionmentioning
confidence: 97%